Increasing experience of ligation of the intersphincteric fistula tract for patients with Crohn's disease: what have we learned?. (2nd August 2017) - Kamiński, J. P.; Zaghiyan, K.; Fleshner, P.
Abstract: Aim: Ligation of the intersphincteric fistula tract (LIFT) has been proposed as a treatment of trans‐sphincteric fistula in perianal Crohn's disease (CD). The aim of this study was to look at our experience of the LIFT procedure in CD patients on long‐term follow‐up. Specifically, we aimed to determine the fistula healing rate after the LIFT procedure after more than 12 months follow‐up and to identify any prognostic factors. Method: Retrospective study of patients with trans‐sphincteric Crohn's fistula tracts treated with the LIFT procedure between January 2011 and October 2015. Complete fistula healing as well as clinical outcomes were analysed. Results: Data were available for 23 patients. After a median follow‐up of 23 months, LIFT site healing was 48%. Patients with healed LIFT had a median follow‐up time of 10.5 months, while patients with failed LIFT had a median follow‐up time of 31 months ( P  =   0.04). Median time to failure was 9 months for patients with follow‐up > 1 year. Most patients failed within 1 year (9/12; 75%) of the procedure. In multi‐site CD, the LIFT procedure was more likely to be successful in those with small bowel disease ( P  =   0.04) compared with colonic disease ( P  =   0.02). Other factors such as preoperative use of biological therapies, presence of a seton, previous repair attempts, fistula position, type or number of fistulas, multiple fistula tracts, smoking status and other associated perianal disease did not appear to influence LIFT healing rates. Conclusion: The LIFT procedure offers reasonable long‐term success in the treatment of perianal trans‐sphincteric fistulas associated with CD. LIFT is more likely to fail in patients with concurrent colonic CD than in patients with small bowel CD.